Synchronization of an inverter to a distributed power network - Parlak, Koray Şener (My University, 2010)
A new method is suggested for the synchronization of an inverter into a distributed power system. The method achieves synchronization of incoming units without any interruption in power flow or any phase shift. In this process there is no any communication signal among inverter units and the incoming units take over load system load related to proportion of their power rating. The method is tested on a system consisting of two three-phase inverters. Results obtained by Matlab-Simulink show promising results. © 2010 IEEE.
2010 International Symposium on Power Electronics, Electrical Drives, Automation and Motion, SPEEDAM 2010 -- 14 June 2010 through 16 June 2010 -- Pisa -- 81684
Keywords: Distributed power system; Load-frequency droop method; Microgrid; Parallel operation of inverters